2020
DOI: 10.1186/s40168-020-00884-z
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota regulates autism-like behavior by mediating vitamin B6 homeostasis in EphB6-deficient mice

Abstract: Background: Autism spectrum disorder (ASD) is a developmental disorder, and the effective pharmacological treatments for the core autistic symptoms are currently limited. Increasing evidence, particularly that from clinical studies on ASD patients, suggests a functional link between the gut microbiota and the development of ASD. However, the mechanisms linking the gut microbiota with brain dysfunctions (gut-brain axis) in ASD have not yet been full elucidated. Due to its genetic mutations and downregulated exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 65 publications
1
60
0
Order By: Relevance
“…Deficits in the gut microbial composition and their metabolic contents such as vitamin and neurotransmitters may be involved in the development of autistic-like social behaviors in these autism mice [ 107 ]. Importantly, children with autism showed a significant improvement in autistic and gastrointestinal symptoms after treatment with fecal microbiota transplantation [ 108 ], and these benefits prolong for years as reported in a follow-up study with the same participants [ 109 ].…”
Section: Influence Of Gut Microbe-regulated Neurotransmitter Synthesis On Cognitionmentioning
confidence: 99%
“…Deficits in the gut microbial composition and their metabolic contents such as vitamin and neurotransmitters may be involved in the development of autistic-like social behaviors in these autism mice [ 107 ]. Importantly, children with autism showed a significant improvement in autistic and gastrointestinal symptoms after treatment with fecal microbiota transplantation [ 108 ], and these benefits prolong for years as reported in a follow-up study with the same participants [ 109 ].…”
Section: Influence Of Gut Microbe-regulated Neurotransmitter Synthesis On Cognitionmentioning
confidence: 99%
“…Last, in line with the ever-increasing interest of the microbiome as a modulator of social behavior [86], accumulating evidence suggest that gut microbiota is involved in the pathogenesis of ASD [77]. Studies show that microbial degradation products found in individuals with ASD elicit autism-like behaviors in mice, possibly through inducing abnormal dopamine metabolism in key structures such as NAc and PFC [87][88][89][90]. Sgritta et al [91] showed that treatment with Lactobacillus reuteri could rescue the behavioral anomalies through modulation of VTA activity via the oxytocinergic system, whereas Li et al [90] managed to ameliorate social deficits through DRD1 agonism in the PFC of mice with disturbed gut microbiota.…”
Section: Dopamine Modulatorsmentioning
confidence: 99%
“…The crosstalk between microbes and host cells is critical for health and regulation of many physiological functions both locally and systemically [ 194 ]. For example, gut microbiota can affect locally regarding the nutrient absorption, vitamin B synthesis [ 195 ], bile acid metabolisms [ 196 ], carbohydrate fermentation [ 197 ], maintenance of barrier integrity [ 55 ], and regulating mucosa immunity [ 198 ] (Figure 6 ). Importantly, the gut microbiota can also systemically impact the host's metabolism, behavioral and cognitive activities [ 199 ], cardiovascular functions [ 200 ], hematopoiesis functions [ 201 ], ageing [ 202 ], inflammation and immunity [ 203 , 204 ], and circadian rhythm [ 205 , 206 ] (Figure 6 ), thereby affecting cancer development and cancer therapeutic efficacy and toxicity [ 140 ].…”
Section: Gut Microbiota and Cancer Therapy Efficacymentioning
confidence: 99%